Embodying the Dharma : Buddhist relic veneration in Asia - Germano, David; Trainor, Kevin (Albany, N.Y. : State University of New York Press, 2004)
Embodying the Dharma explores the centrality of relic veneration in Asian Buddhist cultures. Long disregarded by Western scholars as a superstitious practice reflecting the popularization of "original" Buddhism, relic veneration has emerged as a topic of vital interest in the last two decades with the increased attention to Buddhist ritual practice and material culture. This volume includes studies of relic traditions in India, Japan, Tibet, Sri Lanka, and Thailand, as well as broader comparative analyses, including comparisons of Buddhist and Christian relic veneration.
R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Gautama Buddha -- Relics; Gautama Buddha; Buddhist antiquities -- Asia; Antiquités bouddhiques -- Asie; RELIGION -- Buddhism -- General; Buddhist antiquities; Relics; Asia